Developing a Reflective Deep Learning Module to Enhance Students’ Social Awareness in Cross-Cultural Contexts - Sinta Novia; Dewi Sri Kuning; Anninda Lutfhi Pramuditha (Universitas Islam Negeri Palopo, 2026)
The necessity of equipping students for multicultural interactions has become progressively vital in higher education. Students of English as a Foreign Language (EFL) must develop both linguistic proficiency and reflective awareness, along with social sensitivity, as they engage with culturally diverse contexts. Many learners, however, acquire only theoretical cultural knowledge, lacking introspective skills and emotional insight. This study seeks to develop and assess a reflective deep learning module based on the ADDIE (Analysis, Design, Development, Implementation, Evaluation) framework to improve students' social awareness in cross-cultural settings. Data were acquired using needs analysis questionnaires, reflective journals, interviews, and classroom observations, utilizing a research and development methodology including 24 sixth-semester students in the analysis phase and 10 students in the pilot phase. Research indicates that reflective journaling, case-based learning, role-playing, attentive observation, and experiencing cross-cultural simulations markedly enhanced students' capacity to interpret cultural differences, empathize with others, and respond effectively to intercultural issues. The kids' narratives illustrate a shift from superficial cultural acknowledgment to profound emotional, cognitive, and behavioral understanding. This study enhances the existing research on reflective deep learning as a transformational pedagogical method in EFL teaching, presenting a viable strategy for fostering cross-cultural sensitivity in higher education institutions.